KONTAMINASI MIKROPLASTIK DI USUS DAN INSANG IKAN LAUT KOMERSIAL DARI TELUK JAKARTA - Prasetyo Adi Wibowo, Singgih; Taufik Kaisupy, Muhammad; Reza Cordova, Muhammad (Jurnal Biogenerasi, 2025)
The rapid growth of seafood consumption has raised concerns about food safety due to microplastic contamination in marine organisms. This study investigated the occurrence and characteristics of microplastics in commercially important marine fish marketed in Jakarta Bay, one of Indonesia’s most densely populated and industrialized coastal regions. A total of 160 specimens representing eight species were collected from five major fish markets between December 2023 and January 2024. Microplastics were extracted from gills and gastrointestinal tracts using enzymatic digestion, density separation, and confirmed by ATR-FTIR spectroscopy. Results revealed that 93.8% of the samples contained microplastics, with an average of 3.65 ± 2.34 particles per individual (0.12 ± 0.21 particles/g). Carnivorous and benthopelagic species exhibited significantly higher contamination levels compared to omnivorous and planktivorous species. Most particles were fragments and fibers (~70%), predominantly within the 2000-5000 µm size range. Seven polymer types were identified, with polyethylene, polypropylene, and polystyrene as the most frequent. These findings indicate that Jakarta Bay is a hotspot of plastic pollution, posing potential risks to food security and public health. Continuous monitoring, standardized risk assessments, and improved waste management strategies are urgently needed to mitigate the impacts of microplastic contamination on fisheries and human consumers.